Anti-microbial cream containing arborine/arborinine - Ahmad, Kausar; Mat Ali, Idura; Mohd Hassan, Norazian; ., Maryanto (2011)
Wound infections may endanger the health of a patient if it is untreated. At the site of infection, there may be growth of microorganisms such as bacteria, fungi, or protozoans. Therefore, patients with the infected wounds often had to have a wounded limb removed, or face death from infection. Antimicrobial drugs are normally used to kill the microbes or prevent the growth of the microbes. However, with the development of antimicrobials, many microorganisms have adapted and become resistant to previous discovered antimicrobial agents. The discovery of medicinal plants containing antimicrobial activity such as Glycosmic pentaphylla(Retz.) DC must further be explored to realise the specific active compounds that could portray antimicrobial activity independently. One of the most commonly used dosage form in drug delivery system is cream. Two cream products using refined, bleached and deodorised palm olein containing arborine and arborinine, found in G. pentaphylla, were produced.